Targeted agents in patients with progressive glioblastoma: a systematic meta-analysis of randomized clinical trials - Ippen, Franziska M.; Scherm, Angelika; Keßler, Tobias; Hau, Peter; Agkatsev, Sarina; Baurecht, Hansjörg; Wick, Wolfgang; Knüttel, Helge; Leitzmann, Michael F.; Seliger, Corinna (Cancer medicine, 2024)
Background Glioblastoma (GB) is the most common malignant primary brain tumor in adults and is associated with a poor prognosis. Current treatment guidelines outline the standard of care for patients with newly diagnosed GB; however, there is currently no well-established consensus for the treatment of progressive GB. With this systematic meta-analysis of recently published randomized controlled trials (RCTs), we aim to establish evidence on targeted agents in the treatment of patients with progressive GB. Material and Methods We conducted searches across the Cochrane Library, Pubmed, MEDLINE (Ovid), ClinicalTrials.gov, WHO‘s International Clinical Trials Registry Platform and Google Scholar, encompassing the time span from 1954 to 2022, aiming to identify RCTs evaluating targeted therapies in patients with progressive GB. In order to perform a random-effects meta-analysis, we extracted hazard ratios (HRs) of overall survival (OS) and progression-free survival (PFS). Results We included 16 RCTs (n = 3025 patients) in the systematic meta-analysis. Formally, regorafenib (RR 0.50; 95% CI 0.33-0.75), Depatux-M + TMZ (RR 0.66; 95% CI 0.47-0.93) and rindopepimut + bevacizumab (RR 0.53; 95% CI 0.32-0.88) were associated with an improved OS compared to the control arm. The combination of bevacizumab + CCNU (RR = 0.49; 95% CI 0.35-0.69) and regorafenib (RR 0.65; 95% CI 0.44-0.95) were formally associated with improved PFS. Conclusions The aim of this systematic meta-analysis was to establish evidence for the use of targeted therapies in progressive GB. While some studies demonstrated benefits for OS and/or PFS, those results have to be interpreted with caution as most studies had major methodological weaknesses, including potential differences in sample size, trial design, or the initial distribution of prognostic factors.
Zuerst veröffentlicht: 21. Juni 2024
Gesehen am 25.11.2024